Genetic Polymorphisms of the Coding Region (Exon 6) of Calpastatin in Indonesian Sheep - M I.A Dagong; C Sumantri; R R Noor; R Herman; M Yamin (Faculty of Animal Science, Bogor Agricultural University, 2011)
Calpastatin (CAST) is an indigenous inhibitor of calpain that involved in regulation of protein turn over and growth. The objective of this research was to identify genetic polymorphisms in the entire exon 6 of calpastatin gene in Indonesian local sheep. A PCR-SSCP method was carried out to identify genetic variation of CAST gene. In total 258 heads of local sheep from 8 populations were investigated, three groups of samples were Thin Tail Sheep (TTS) from Sukabumi, Jonggol, and Kissar. The rest samples were Priangan sheep (PS) from Margawati (Garut meat type) and Wanaraja (Garut fighting type) and Fat Tail Sheep (FTS) from Donggala, Sumbawa, and Rote islands. SSCP analysis revealed that three different SSCP patterns corresponded to three different alleles in the CAST locus (CAST-1, 2, and 3 allele) with five different genotypes. Genetic variation between local sheep populations were calculated based on genotypic and allelic frequencies. Most populations studied were polymorphic, with genotype frequencies of CAST-11, CAST-12, CAST-22, CAST-32, and CAST-33 were 0.286, 0.395, 0.263, 0.046, and 0.007 respectively. CAST-1 and 2 alleles were most commonly found in all populations with total frequency was 0.970, while CAST-3 was a rare allele 0.030 and only found in TTS population. Variation in the CAST gene could be used for the next research as genetic diversity study or to find any association between CAST polymorphism with birth weight, growth trait and carcass quality in Indonesian local sheep.